2019
DOI: 10.2486/indhealth.2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

SOS—Appreciation overboard! Illegitimacy and psychologists’ job satisfaction

Abstract: In the globalized and rapidly evolving work environment, deficiencies in job design are a common reason that employees must sometimes complete tasks that are not directly connected to their occupational role. Individuals with a clear vision of their occupational role and duties in particular, such as psychologists, might consider such tasks as an offense to self. According to the “Stress-as-Offense-to-Self” (SOS) concept, so-called “illegitimate tasks” do not respect a person’s occupational identity—threatenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 71 publications
(124 reference statements)
3
20
0
Order By: Relevance
“…Possibly, the identification with one’s job is so strong among GPs that it results in a major overlap between life and job satisfaction. The association between illegitimate tasks and job satisfaction is in line with previous studies [ 17 , 30 ]. Administrative tasks are risk factors for reduced job satisfaction [ 27 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Possibly, the identification with one’s job is so strong among GPs that it results in a major overlap between life and job satisfaction. The association between illegitimate tasks and job satisfaction is in line with previous studies [ 17 , 30 ]. Administrative tasks are risk factors for reduced job satisfaction [ 27 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that GPs more often report unnecessary than unreasonable tasks is in line with other studies [ 31 ]. A comparison of our results with the findings of studies among other occupational groups suggests that GPs are more strongly affected by illegitimate tasks than other professions [ 17 , 29 , 31 ]. Our study adds evidence to previous findings that illegitimate tasks affect health outcomes [ 29 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, beyond such legitimate tasks that come from a different professional field yet, the solo self-employed also reported being in charge of tasks that are either perceived as unreasonable (1b; misaligned with occupational role) or unnecessary (1c; dictated from outside). Both kinds of tasks must be evaluated as illegitimate tasks (Semmer et al, 2015) as they should not be expected from the person and contain an element of a lack of appreciation (Kottwitz et al, 2019b) leading to mental impairment (Semmer et al, 2015).…”
Section: Demands Arising In Solo Self-employmentmentioning
confidence: 99%
“…Pereira finds that illegitimate tasks are negatively related to sleep quality; specifically, they are positively related to sleep fragmentation and sleep latency ( Pereira et al, 2014 ). Illegitimate tasks are also negatively correlated with job satisfaction ( Omansky et al, 2016 ; Kottwitz et al, 2019 ; Ilyas et al, 2021 ). Moreover, it has been shown that illegitimate tasks are correlated with work-to-family conflict ( Jacobshagen, 2006 ), and Zhou et al (2020) reports an indirect effect of illegitimate tasks on work-to-family conflict via psychological detachment.…”
Section: Introductionmentioning
confidence: 99%